2021
DOI: 10.1371/journal.pone.0245036
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness and affordability of prescriptions to diabetic patients attending a tertiary hospital in Eastern Uganda: A retrospective cross-sectional study

Abstract: Background Irrational prescription of drugs can lead to high cost of treatment thus limiting access to essential medicines. We assessed the affordability and appropriateness of prescriptions written for diabetic patients in Eastern Uganda. Methods We collected secondary data from the health management information system registers of patients who attended the outpatient medical clinic at Mbale regional referral hospital from January 2019 to December 2019. The average cost of the prescriptions was calculated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Out of pocket expenses have been shown to be a significant in impeding access to and retention in NCD care in Africa. A study in eastern Uganda among users with an NCD showed that over 92% of the diabetic users were unable to afford drugs purchases and this increased their rates of multi-morbidity [47]. Other research showed that NCD users in Uganda were found to be unable to afford the cost of care [48] and faced significant geographical constraints to accessing services [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Out of pocket expenses have been shown to be a significant in impeding access to and retention in NCD care in Africa. A study in eastern Uganda among users with an NCD showed that over 92% of the diabetic users were unable to afford drugs purchases and this increased their rates of multi-morbidity [47]. Other research showed that NCD users in Uganda were found to be unable to afford the cost of care [48] and faced significant geographical constraints to accessing services [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…The accessibility of care related-enablers for the implementation of both the EDL 96, 98, 103 and EML 48, 50, 53, 57, 64, 68, 69, 79, 83–85, 87, 104, 128, 133, 134 , are opposite to the barriers listed above.…”
Section: Resultsmentioning
confidence: 92%
“…The barriers related to the relationship with norms and standards for the EDL implementation included poor availability of diagnosis and management guidelines, noting the unavailability of diabetes guidelines in any surveyed clinics 165 . Other barriers unique to the EML included incompliance to guidelines 50,53,131,149,153,166,168,169 , incompliance to national EMLs 48,68,79,132,145,170 , lack of national EMLs in facilities 128,171 , disconnect between guidelines on treatment protocols 47,75 , disconnect between policy, guidelines and practice 46,167 , and lack of standard operating procedures 135 .…”
Section: Relationship With Norms and Standardsmentioning
confidence: 99%
“…In Uganda, long-acting insulin analogues including insulin glargine are currently not listed in the Ugandan EML ( Table 1 ). This is a concern in view of the high rates of hypoglycaemia currently seen; however, reflects issues of affordability in Uganda, which is a major issue ( 115 ). Currently, prices for insulin glargine within the healthcare system in Uganda vary between US$15–$35/pen depending on whether this is a biosimilar or originator, and whether hospital or community pharmacy.…”
Section: Resultsmentioning
confidence: 99%